Securing the Cloud: Privacy, Policy, and AI-Driven Cybersecurity Solutions - Rinaldo (Indonesian Scientific Publication, 2024)
As cloud computing becomes the backbone of modern digital infrastructure, cybersecurity has emerged as a critical concern across public and private sectors. This narrative review investigates the multifaceted threats, defense strategies, and policy implications associated with cybersecurity in the cloud environment. Literature was systematically sourced from Scopus and Google Scholar using keywords such as